Zatoichi meets the one-armed swordsman [videorecording (DVD)] - Yasuda, Kimiyoshi, 1911-1983; Yasuda, Kimiyoshi, 1911-1983; Katsu, Shintarō, 1931-1997; Katsu, Shintarō, 1931-1997; Hamada, Yūko; Wang, Yu, 1944-; Shimozawa, Kan, 1892-1968 (AnimEigo, 2004)
"On the outskirts of the town of Furukawa, blind masseur and master blade-slinger Zatoichi encounters one-armed Chinese martial artist Wang Kang and a young boy. Discovering that the pair are on the run from the corrupt local Samurai, murderers of the boy's parents, Zatoichi agrees to guide them to a nearby temple. Unfortunately, things are never that easy for the blind man, as he becomes entangled in in a struggle to save not only these two, but also the lives of the people they come across. When the situation worsens, Zatoichi may discover that his greatest enemy is not the men sent to kill the party, but Wang Kang and a lack of a common language between the two of them. As the crisis escalates, the two master swordsmen will find themselves alone in a confrontation where only one will walk away alive!" The 22nd movie in the series.